Oncology Nurse Managers' Perceptions of Palliative Care and End-of-Life Communication. (May 2019) - Sawin, Kathleen J.; Montgomery, Kathleen E.; Dupree, Claretta Yvonne; Haase, Joan E.; Phillips, Celeste R.; Hendricks-Ferguson, Verna L.
The purpose of this study was to describe pediatric oncology nurse managers' (NMs) perspectives of palliative care/end-of-life (PC/EOL) communication. The study, guided by group-as-a-whole theory and empirical phenomenology, was part of a larger, multisite study aimed at understanding pediatric oncology nurses' experiences of PC/EOL communication. Nurses were assigned to focus groups based on length or type of experience (i.e., nurses with <1, 2–5, or >5 years' work experience and NMs). Eleven NMs from three Midwestern pediatric hospitals with large oncology programs participated in one focus group. The participants' mean years of experience was 15.8 in nursing and 12 in pediatric oncology; 90% had a BSN or higher degree; all had supervisory responsibilities. The authors identified 2, 912 meaning statements, which were then analyzed using Colaizzi's method. Findings include NMs' overall experience of "Fostering a Caring Climate, " which includes three core themes: (1) Imprint of Initial Grief Experiences and Emotions; (2) Constant Vigilance: Assessing and Optimizing Family-Centered Care; and (3) Promoting a Competent, Thoughtful, and Caring Workforce. Findings indicate that pediatric oncology NMs draw on their own PC/EOL experiences and their nursing management knowledge to address the PC/EOL care learning needs of nursing staff and patient/family needs. NMs need additional resources to support nursing staff's PC/EOL communication training, including specific training in undergraduate and graduate nursing programs and national and hospital-based training programs.